Antioxidant study of methanolic and ethanolic extracts of Malaysian aromatic plants’ leaves: towards industrial biotechnology - Kamarudin, Kamarul Rahim; Abu Abas, Azlim Almey; Koya, Mustapha Suleiman; Syed Osman Idid, Syed Zahir Idid; Mohamed Rehan, Aisyah; Khan Chowdhury, Ahmed Jalal (2010)
The aim of this study is to determine the antioxidant properties of methanolic and ethanolic extracts of four Malaysian aromatic plants’ leaves, namely knotweed (Polygonum minus), curry (Murraya koenigii), kaffir lime (Citrus hysrix) and fragrant screwpine (Pandanus odurus) as a head start for industrial biotechnology. Total phenolic content (TPC) assay using Folin-Ciocalteu method was used to assess the presence and level of phenolic compounds in each sample. Antioxidant activity in terms of total antioxidant and free radical scavenging activities of both methanolic and ethanolic extracts was measured by β-carotene bleaching assay and 2, 2, diphenyl-1- icrylhydrazyl (DPPH) free radical scavenging activity assay, respectively. The present results showed that methanolic extract of P. minus exhibited the highest total antioxidant activity (98.2 ±0.5%) while for the EC50 based on DPPH. radical scavenging activity assay, the lowest concentration was shown by P. minus extracts as compared to the other samples. For both ethanolic and methanolic extracts, moderately strong and strong positive correlations existed between the phenolic content and antioxidant activity based on β-carotene bleaching assay, respectively. Among the eluent systems used for phytochemical analysis using thin layer chromatography (TLC), EWFA showed the largest number of antioxidant active compounds, followed by EMW and CEF. HEA eluent system indicated no presence of antioxidant active compound showing that most compounds were polar. Retardation factor (Rf) values were calculated between 0.2 to 0.6. Relatively, the present results suggested that of the four aromatic plants, P. minus and M. koenigii have high potential as sources of commercial natural antioxidants regardless types of extracting solvents.